Answer:
We need to put x = -4 where the question mark lies.
Step-by-step explanation:
Given the expression
[tex]\left(x^6\right)^0=x^4\cdot \:\:x^?[/tex]
First, solve the left-hand side of the equation
[tex]\left(x^6\right)^0[/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \:a^0=1,\:\quad \:a\ne \:0[/tex]
Thus, the expression becomes
[tex]\left(x^6\right)^0=1[/tex]
So we have to put the number which can make the right-hand side of the equation equal to 1.
Let's put x = 4 where the question mark lies and solve the equation to check whether the right-hand side of the equation becomes 1.
[tex]x^4\cdot \:\:x^{-4}[/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^{b+c}[/tex]
[tex]=x^{4-4}[/tex]
[tex]=x^0[/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \:a^0=1,\:\quad \:a\ne \:0[/tex]
[tex]=1[/tex]
Thus, both equations become equal when we put x = -4 on the question mark.
[tex]\left(x^6\right)^0=x^4\cdot \:\:x^{-4}[/tex]
[tex]1=1[/tex]
Therefore, we need to put x = -4 where the question mark lies.